Episodic warming of near‐bottom waters under the Arctic sea ice on the central Laptev Sea shelf. Issue 1 (14th January 2016) - Janout, Markus; Hölemann, Jens; Juhls, Bennet; Krumpen, Thomas; Rabe, Benjamin; Bauch, Dorothea; Wegner, Carolyn; Kassens, Heidemarie; Timokhov, Leonid
Abstract: A multiyear mooring record (2007–2014) and satellite imagery highlight the strong temperature variability and unique hydrographic nature of the Laptev Sea. This Arctic shelf is a key region for river discharge and sea ice formation and export and includes submarine permafrost and methane deposits, which emphasizes the need to understand the thermal variability near the seafloor. Recent years were characterized by early ice retreat and a warming near‐shore environment. However, warming was not observed on the deeper shelf until year‐round under‐ice measurements recorded unprecedented warm near‐bottom waters of +0.6°C in winter 2012/2013, just after the Arctic sea ice extent featured a record minimum. In the Laptev Sea, early ice retreat in 2012 combined with Lena River heat and solar radiation produced anomalously warm summer surface waters, which were vertically mixed, trapped in the pycnocline, and subsequently transferred toward the bottom until the water column cooled when brine rejection eroded stratification. Key Points: Mooring record reveals episodic bottom water warming events under the Laptev Sea ice in winter Solar warming during early ice retreat impacts surface‐to‐bottom waters and possibly permafrost Combination of mixing and advection controls near‐bottom warming